Clinical and surgical consequences of the COVID-19 pandemic for patients with pediatric urological problems: Statement of the EAU guidelines panel for paediatric urology, March 30 2020. Issue 3 (June 2020) - Quaedackers, Josine S.L.T.; Stein, Raimund; Bhatt, Nikita; Dogan, Hasan Serkan; Hoen, Lisette; Nijman, Rien J.M.; Radmayr, Christian; Silay, Mesrur Selcuk; Tekgul, Serdar; Bogaert, Guy
Summary: The COVID-19-pandemic forces hospitals to reorganize into a dual patient flow system. Healthcare professionals are forced to make decisions in patient prioritization throughout specialties. Most pediatric urology pathologies do not require immediate or urgent care, however, delay may compromise future renal function or fertility. Contact with patients and parents, either physical in safe conditions or by (video)telephone must continue. The Paediatric-Urology-Guidelines-panel of the EAU proposes recommendations on prioritization of care. Pediatric-Urology program directors must ensure education, safety and attention for mental health of staff. Upon resumption of care, adequate prioritization must ensure minimal impact on outcome.